1967
DOI: 10.1126/science.157.3796.1524
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylation-Induced Migration: The NIH Shift

Abstract: have been discussed by Cameron (32), Johnson (33), Manley (34), and Matsuoka et al. (35).On the basis of the rather crude x-ray positional data that were available in the fall of 1966, Sandage made a photographic survey of a 4by 4-degree region surrounding Cyg XR-2. Subsequently, more accurate information was provided by the ASE-MIT group, which led to an identification of Cyg XR-2 with a 16th-magnitude blue star noted on the Palomar plates. If the identification is confirmed, Cyg XR-2 and Sco XR-1 will be "ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
193
0
2

Year Published

1969
1969
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(203 citation statements)
references
References 27 publications
8
193
0
2
Order By: Relevance
“…It was once suspected that hydroxylation of PBDEs was mediated by cytochrome P450 enzymes, which could account for direct hydroxylation or hydroxylation via a 1,2-shift. In addition, the 1,2-shift mechanism proceeded via an arene oxide intermediate (Guroff et al, 1967;Jerina and Daly, 1974). Moreover, previous studies suggested that orthosubstituted OH-BDEs were formed from naturally occurring compounds in marine ecosystems (Teuten et al, 2005), while meta-or para-substituted OH-BDEs could originate from the biotransformation of synthetic BDEs (Malmberg et al, 2005;Hamers et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was once suspected that hydroxylation of PBDEs was mediated by cytochrome P450 enzymes, which could account for direct hydroxylation or hydroxylation via a 1,2-shift. In addition, the 1,2-shift mechanism proceeded via an arene oxide intermediate (Guroff et al, 1967;Jerina and Daly, 1974). Moreover, previous studies suggested that orthosubstituted OH-BDEs were formed from naturally occurring compounds in marine ecosystems (Teuten et al, 2005), while meta-or para-substituted OH-BDEs could originate from the biotransformation of synthetic BDEs (Malmberg et al, 2005;Hamers et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We would even postulate that its presence is indicative of a sufflicient production of DHPPA or VPA to interfere with the normal metabolism of tyrosine. The major metabolite of tyrosine metabolism is p-hydroxyphenylpyruvic acid (p-HPPA) which is normally further metabolized by p-HPPA-oxidase (La Du, 1966), undergoing the recently described "NIH shift " (Guroff, Daly, Jerina, Renson, Witkop & Udenfriend, 1967), to 2,5-dihydroxy,phenylacetic acid (homogentisic acid). Our finding of an increased output of the immediate reduction product of p-HPPA, p-HPLA, which tends to correlate with VLA output, suggests to us that DHPPA or VPA may compete with p-HPPA for p-HPPA-oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison can be made with hydroxylation of aryl compounds and the 1,2-"NIH shift" (i.e. p to m shift of hydrogen due to a 4-keto intermediate) (58), although in the case of aryl compounds, the epoxides are often unstable, and demonstrating a "non-epoxide" mechanism is difficult. Precedent also exists for 1,2-halide migration in the conversion of vinyl halides to carbonyls without the intermediary of epoxides (38,59).…”
Section: -Ketocholesterol Formation By Cytochrome P450 7a1mentioning
confidence: 99%